Efeitos da energia elétrica em uma aldeia A’uwẽ/Xavante: o caso da aldeia Etenhiritipá - Abreu, Mariana Monteiro de (Universidade Federal de São Carlos, 2022)
This dissertation focuses on some of the effects of electricity in an A’uwẽ/Xavante Etenhiritipá village after the implementation by the Federal Government of the rural electrification program known as Luz Para Todos, in 2012. Doing fieldwork in the Etenhiritipá village from its foundation to the installation of electrical energy, I seek to understand how A’uwẽ/Xavante way of life, as they understand it, was modified or enhanced with its use, highlighting the various practices in which it is adopted, defining new relationships on diverse ways, and how this community, despite the risks, much of them they recognize themselves, others are learning to deal with strategically uses it in order to promote their permanence as A’uwẽ/Xavante in the world.
Effects of electricity in an A'uwẽ/Xavante village: the case of the Etenhiritipá village
Keywords: A’uwẽ/Xavante; Efeitos; Luz para todos; Territorialidade; História; Effects; Territoriality; History; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA; CIENCIAS HUMANAS::ANTROPOLOGIA; CIENCIAS SOCIAIS APLICADAS::ARQUITETURA E URBANISMO